Examining the Impact of Certificate of Need Laws on the Utilization and Reimbursement of Cataract Surgeries Among Medicare Beneficiaries - Alvina Liang; Jennifer L. Lindsey (Journal of Health Economics and Outcomes Research)
**Background:** Cataract surgery is an effective and commonly utilized procedure and can significantly improve quality of life and restore economic productivity. Certificate of need (CON) laws aim to regulate healthcare facility expansion and equipment acquisition to curtail costs, enhance quality, and ensure equitable access to care. However, little is known about the impact of CON laws on cataract surgery utilization and reimbursement.